SOCIO-RELIGIOUS REFORM MOVEMENTS AS AGENTS OF COMMUNAL HARMONY IN MODERN INDIA - Shabir Ahmad Lone; V.Thirumurugan (PT. Radja Intercontinental Publishing, 2025)
The interplay between socio-religious reform movements and communal harmony has been a pivotal aspect of societal transformation throughout history. Socio-religious reform movements, often arising during periods of social and political upheaval, have played critical roles in addressing and mitigating social inequalities, religious intolerance, and communal discord. This article delves into the historical context, philosophical underpinnings, and impacts of various socio-religious reform movements on fostering communal harmony, particularly in the Indian subcontinent. The 19th and early 20th centuries witnessed significant socio-religious reform movements across different cultures and religions. In India, movements such as the Brahmo Samaj, Arya Samaj, Ramakrishna Mission, self-respect movement, and the Aligarh Movement aimed to reform societal norms, religious practices, and education systems. The reform movements were not limited to Hinduism and Islam; they also encompassed efforts within Christianity, Sikhism, and other religions. The Christian missionaries, while introducing Western education and healthcare, also advocated for social reforms like the abolition of untouchability and the upliftment of marginalized communities. These movements promoted education and rational thinking, which helped dispel myths, superstitions, and prejudices that often fuelled communal tensions. By advocating for universal education, reformers ensured that people from different communities could interact and learn from each other, thus building mutual respect and understanding. The reform movements addressed social injustices and inequalities that were often at the root of communal conflicts. These movements contributed to creating a more just and equitable society by fighting against practices such as untouchability, sati, and child marriage, as well as promoting the rights and dignity of women and marginalised communities. Socio-religious reform movements have played a crucial role in promoting communal harmony by addressing social inequalities, promoting education and rational thinking, and fostering interfaith dialogue. The article underscores the need for sustained efforts to build on the legacy of these reform movements to ensure a just, equitable, and harmonious society.